Efficiency of elastomeric isolators in reducing seismic acceleration in the base of reinforced concrete buildings subjected to Peruvian seismic records - Oviedo Sarmiento, Ricardo (2022)
The present work seeks to determine how the efficiency of elastomeric isolators influences the reduction of seismic acceleration in the base of reinforced concrete buildings subjected to Peruvian seismic records. Methodology: Applied type study, based on the ASCE/SEI 7-22 code and on the Technical Standard E.031-19. Results: The following were considered: 03 elastomeric insulators: Lead core, High damping and Natural rubber; 03 types of floors: Rigid Floor S1, Intermediate Floor S2 and Flexible Floor S3; 02 seismic zones: Zone 4 (0.45) and Zone 3 (0.35); 02 periods of vibration of structural systems: Reinforced concrete frames and walls; 01 type of overload: buildings (200 kg/cm2); 03 values of the rubber shear modulus: lower limit, intermediate limit and upper limit; and, 20 reinforced concrete buildings with different levels: from 01 to 20 levels. Conclusion: Elastomeric isolators influence the reduction of seismic acceleration in the base of reinforced concrete buildings subjected to Peruvian seismic records, because elastomeric isolators with a lead core, high damping and natural rubber reduce seismic acceleration.